MODEL DESENTRALISASI DUAL CHANNEL CLOSED-LOOP SUPPLY CHAIN DENGAN PROSES DAUR ULANG PIHAK KETIGA DAN WAKTU TUNGGU PENGIRIMAN - Setiyowati, Ririn; Sutanto, Sutanto; Winaro, Bowo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Dual channel closed loop supply chain (DC-CLSC) is a mathematical model that describes a set of supply chain activities that use two sales channel and used products that have been used by consumers back to manufacturer. In this research, the DC-CLSC model was developed with third-party recycling process and delivery lead time. The model obtained is used to determine the optimal decision variables consisting of wholesale prices, price in the online channel, price from retailers, rewards given to third parties, and the recovery rate. Based on the results of optimal solution and numerical simulation he model obtained is used to determine the optimal decision variables consisting of wholesale prices, prices in the online channel, prices from retailers, rewards given to third parties, and the recovery rate.